Anatolii F. Grishin (obituary) - MarchenkoІ. І.; Korobov, V. I.; Gordevskyy, V. D.; Rezounenko, A. V. (Visnyk of V. N. Karazin Kharkiv National University. Ser. Mathematics, Applied Mathematics and Mechanics, 2015)
Anatolii F. Grishin (obituary). [ September 9, 1941 - February 10, 2015 ]